2011
DOI: 10.1002/cncr.26387
|View full text |Cite
|
Sign up to set email alerts
|

Relative survival of childhood and adult medulloblastomas and primitive neuroectodermal tumors (PNETs)

Abstract: BACKGROUND: Medulloblastomas are 1 of the most common brain tumors in children but can affect individuals of all ages. For this report, the author investigated the impact of medulloblastomas/primitive neuroectodermal tumors (PNETs) on the US population with a focus on age differences. METHODS: Data from the Surveillance, Epidemiology, and End Results (SEER) database were used to describe cumulative relative survival (CRS) using crude, period, and longitudinal period approaches for patients diagnosed with all m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
79
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 37 publications
3
79
0
1
Order By: Relevance
“…In our study we did not find a difference in survival between the TYA age group and children aged 5-9 years. We did however observe a doubling of the risk of death for those aged under 5 years, consistent with other studies (3,5,(15)(16)(17)(18)(19)31) due to treatment strategies for infants and young children that defer or avoid radiation (7).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In our study we did not find a difference in survival between the TYA age group and children aged 5-9 years. We did however observe a doubling of the risk of death for those aged under 5 years, consistent with other studies (3,5,(15)(16)(17)(18)(19)31) due to treatment strategies for infants and young children that defer or avoid radiation (7).…”
Section: Discussionsupporting
confidence: 91%
“…We compared our survival rates to those from other international studies and found childhood medulloblastoma rates are similar to those in France (16) and Sweden (15) (17). In our study we did not find a difference in survival between the TYA age group and children aged 5-9 years.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Male gender has been identified as a risk factor for medulloblastomas, PNETs, AT/RTs, neuroblastomas, and hepatoblastomas in this and other studies. [14][15][16][17][18] The exceptions to the male predominance were Wilms tumors, as shown by others as well, 19 and ganglioneuroblastomas. A strongly diverging median age at diagnosis between the genders was detected for PNET and medulloepitheliomas, which may reflect greater biological differences between the genders for these tumors than for the others.…”
Section: Discussionmentioning
confidence: 95%